2015
DOI: 10.1175/jcli-d-14-00422.1
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Relationship between Interannual Variations of the North Atlantic Oscillation and Northern Tropical Atlantic SST

Abstract: The relationship between interannual variations of boreal winter North Atlantic Oscillation (NAO) and northern tropical Atlantic (NTA) sea surface temperature (SST) experienced obvious interdecadal changes during 1870–2012. Similar interdecadal changes are observed in the amplitude of NTA SST anomalies. The mean NTA SST change may be a plausible reason for several changes in the NAO–NTA SST connection. Under a higher mean NTA SST, NTA SST anomalies induce larger wind anomalies over the North Atlantic that prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 53 publications
2
61
0
Order By: Relevance
“…This may be attributed to the nonlinearity of dependence of atmospheric heating on the mean temperature, as demonstrated by previous studies (e.g. Ham and Kug, ; Chen et al , ; Cao et al , ). Furthermore, stronger zonal SST gradient and warmer total SST in far west equatorial Pacific (to the west of 140°E) in CP La Niña events than those in the EP La Niña events may also contribute to a stronger atmospheric response for the CP La Niña winter (Figure ).…”
Section: Atmospheric Circulation Anomaly Patterns For Two Types Of Lamentioning
confidence: 98%
“…This may be attributed to the nonlinearity of dependence of atmospheric heating on the mean temperature, as demonstrated by previous studies (e.g. Ham and Kug, ; Chen et al , ; Cao et al , ). Furthermore, stronger zonal SST gradient and warmer total SST in far west equatorial Pacific (to the west of 140°E) in CP La Niña events than those in the EP La Niña events may also contribute to a stronger atmospheric response for the CP La Niña winter (Figure ).…”
Section: Atmospheric Circulation Anomaly Patterns For Two Types Of Lamentioning
confidence: 98%
“…Previous studies suggested that the variation in precipitation over China can also be related to SST anomalies (SSTAs) in the North Atlantic (NA; e.g., Chen et al, ; Song et al, ; Sun & Wang, , ; Wu et al, 2009; Wu et al, ; Wu & Kirtman, ). Some studies have revealed that during winter when the North Atlantic Oscillation (NAO) is most active, there is a close interaction between the NAO and underlying SST in the NA sector through the exchange of sensible and latent heat fluxes (e.g., Bjerknes, ; Cayan, ; Frankignoul & Kestenare, ; Hurrell, ; Peng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Song et al () suggested that there are two different pathways that the NAO‐associated stationary Rossby wave trains propagate downstream in winter. However, some studies revealed that the connection between the NA SSTAs and downstream climate anomalies is unstable (e.g., Chen et al, ; Walter & Graf, ; Wu et al, ). Walter and Graf () revealed that the relationship between the winter NA SSTAs and the regional circulation anomalies has strengthened since the late 1960s.…”
Section: Introductionmentioning
confidence: 99%
“…The major modes of summer Chinese climate are markedly influenced by the state of the NAO through changes in the position of the North Atlantic storm track and transient eddy activity (Linderholm et al ., ). Changes in the sea surface temperature (SST) over the North Atlantic also correlate well with the NAO (Wallace et al ., ; Marshall et al ., ; Czaja and Frankignoul, ; Cassou et al ., ; Gu et al ., ; Chen et al ., ; Chen et al ., ). Marshall et al .…”
Section: Introductionmentioning
confidence: 97%